Web Based Distribution of Zakat, Infaq, and shodaqoh (Case Study Of Surakarta City Region) - Ihsan Cahyo Utomo; Siti Rokhmah; muqorobin muqorobin; Isnawati Muslihah (International Journal of Computer and Information System (IJCIS), 2020)
Abstract— Zakat is one of the pillars of Islam whose implementation is required for all Muslims whose wealth meets the Nisab. Nisab is a standard of property that must be Zakati. Because Zakat is the property of the people, the management must be properly channeled. Surakarta city is one of the major cities in Indonesia, there are several institutions of amil Zakat in the city of solo. However, there is no data on the distribution of Zakat in the integrated solo city, so that there are still many recipients of Zakat who receive alms from several amil Zakat. In this study, mapping of Zakat, Infaqand shadaqoh mapping was carried out with a Geographical Information System (GIS). This study aims to produce a deeper analysis of the socioeconomic life in the city of Surakarta as a basis for mapping the distribution of Zakat, Infaq, andShodaqoh. The method used to collect data with rapid appraisal. Where rapid appraisal is a method used to collect data based on socio-economic conditions in the environment, so as to produce a picture of mapping the distribution of Zakat, Infaq, andShodaqoh which is used as a reference for amil Zakat institutions in the Surakarta region to spread.